2017
DOI: 10.1111/2041-210x.12829
|View full text |Cite
|
Sign up to set email alerts
|

The power of 3D fractal dimensions for comparative shape and structural complexity analyses of irregularly shaped organisms

Abstract: The increasing interest in 3D morphological approaches for addressing evolutionary and ecological questions has driven the need for reliable, efficient, and easily accessible methods for shape quantification and complexity characterization. This applies in particular to irregularly shaped organisms, such as stony corals, which are challenging to study using traditional morphometric analyses. A potential approach to assess shape and spatial complexity of 3D documented organisms are 3D fractal dimension analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 52 publications
(84 reference statements)
1
69
1
Order By: Relevance
“…Higher fractal dimensions lead to more convoluted surfaces or perimeters with a larger number of wrinkles and textures that increase the effective surface and perimeter of corals (Falconer, 2003; Okie, 2013). Previous studies found fractality among corals at different scales (Basillais, 1997; Bradbury & Reichelt, 1983; Knudby & LeDrew, 2007; Martin-Garin et al, 2007; Mark, 1984; Purkis et al, 2006; Reichert et al, 2017; Zawada & Brock, 2009), but the measurements at the coral colony scale of interest in the present study were inconclusive (Mark 1984).…”
Section: Introductioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Higher fractal dimensions lead to more convoluted surfaces or perimeters with a larger number of wrinkles and textures that increase the effective surface and perimeter of corals (Falconer, 2003; Okie, 2013). Previous studies found fractality among corals at different scales (Basillais, 1997; Bradbury & Reichelt, 1983; Knudby & LeDrew, 2007; Martin-Garin et al, 2007; Mark, 1984; Purkis et al, 2006; Reichert et al, 2017; Zawada & Brock, 2009), but the measurements at the coral colony scale of interest in the present study were inconclusive (Mark 1984).…”
Section: Introductioncontrasting
confidence: 77%
“…Corals with mean fractal dimensions smaller than two, DS < 2, displayed surfaces with holes and large peninsulas, while corals with fractal dimensions larger than two, DS > 2, displayed more compact surfaces with richer and more wrinkled textures (Figure 3c). Additional geometric metrics such as rugosity, vector dispersion, multivariate multiscale fractal dimension, and multifractal analysis (Reichert et al, 2017; Young et al, 2017, Chakraborty et al, 2016) might be necessary to refine the coral geometric analysis presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Fractal dimension has been previously suggested as a matric for quantifying the shapes of corals or structural complexity of coral reefs [15,[34][35][36]. Fractal dimension (D) was calculated as D = 2 − slope logS(δ)/log(δ), in which δ is a resolution of the raster and S(δ) is the 3D surface area at the given resolution [15].…”
Section: R Proceduresmentioning
confidence: 99%
“…However, while these results highlight differences between growth forms across a range of processes, they are unable to directly assess process-based hypotheses for the observed differences, nor can the results be generalised to other growth forms or taxa with similar morphological adaptations but different overall morphology (e.g., sponges, hydrozoans, algae, plants, etc). As such, recent studies have begun to explore techniques for quantifying and comparing the three-dimensional shape of corals (Lavy et al 2015;Reichert et al 2017;Bythell, Pan, and Lee 2001;House et al 2018). We build on this work to develop a quantitative schema for coral morphology via variables that capture shape variation.…”
Section: Introductionmentioning
confidence: 99%